Externally Silylated RH-MCM-48 from Rice Husk Silica with Superparamagnetic Iron Oxide for Multifunctional Applications - Suyanta, S. (Asian Publication Corporation, 2022)
Rice husk silica has been used as a raw material for the sonochemical synthesis of MCM-48 (RH-MCM-48). Silylation on the outer surface of RH-MCM-48 using trimethylchlorosilane before removal of the template to prevent the formation of iron oxide in the outer of RH-MCM-48. The impregnation of Fe3+into the externally silylated-RH-MCM-48 porous system was done by optimizing the concentration of Fe3+, contact time and temperature. The XRD pattern, N2adsorption/desorption isotherms and TEM images showed that RH-MCM-48 has an ordered Ia3d cubic mesostructure with high specific surface area and narrow porous size distribution. FTIR spectra confirmed the successful implementation of external silylation. Moreover, DR-UV-vis spectra, EPR spectra and magnetization curve show that the impregnation of Fe3+into the externally silylated-RH-MCM-48 pores produce a superparamagnetic iron oxide nanoparticles formed inside the pores and induces partial isomorphic substitution of Si4+by Fe3+on the wall pores.